2009
DOI: 10.1128/iai.01048-08
|View full text |Cite
|
Sign up to set email alerts
|

Human Microbiota-Secreted Factors Inhibit Shiga Toxin Synthesis by Enterohemorrhagic Escherichia coli O157:H7

Abstract: Escherichia coli O157:H7 is a food-borne pathogen causing hemorrhagic colitis and hemolytic-uremic syndrome, especially in children. The main virulence factor responsible for the more serious disease is the Shiga toxin 2 (Stx2), which is released in the gut after oral ingestion of the organism. Although it is accepted that the amount of Stx2 produced by E. coli O157:H7 in the gut is critical for the development of disease, the eukaryotic or prokaryotic gut factors that modulate Stx2 synthesis are largely unkno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(75 citation statements)
references
References 38 publications
3
70
0
1
Order By: Relevance
“…4C). The anaerobic microbiota of the gut, and of B. thetaiotaomicron in particular, secretes soluble factors that inhibit Stx production (31). Elimination of anaerobic microbes via H 2 O 2 would be another mechanism by which XO regulates virulence.…”
Section: Discussionmentioning
confidence: 99%
“…4C). The anaerobic microbiota of the gut, and of B. thetaiotaomicron in particular, secretes soluble factors that inhibit Stx production (31). Elimination of anaerobic microbes via H 2 O 2 would be another mechanism by which XO regulates virulence.…”
Section: Discussionmentioning
confidence: 99%
“…A further exploration of the interactions between E. coli O157:H7 and the plethora of bacterial species present in the gut is needed to appreciate how the gut microbiome affects the virulence of this foodborne pathogen. It was also shown previously that fecal Bacteroides thetaiotaomicron alters Stx2 expression (40)(41)(42), although two studies (40,42) report decreases while one (41) report shows Hematoxylin-and eosin-stained renal sections from mice infected with either C600 or PA2 and PA2 plus C600. The mice were scored as described in Materials and Methods.…”
Section: Figmentioning
confidence: 99%
“…Various studies have suggested that probiotics or their secreted factors such as organic acids downregulate the transcriptional levels of virulence genes in E. coli O157:H7, 5,9,10,24) but the specific role of probiotics in L. monocytogenes virulence-related gene expression has not been well described.…”
Section: Discussionmentioning
confidence: 99%